2023
DOI: 10.2196/43726
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm to Classify Real-World Ambulatory Status From a Wearable Device Using Multimodal and Demographically Diverse Data: Validation Study

Abstract: Background Measuring the amount of physical activity and its patterns using wearable sensor technology in real-world settings can provide critical insights into health status. Objective This study’s aim was to develop and evaluate the analytical validity and transdemographic generalizability of an algorithm that classifies binary ambulatory status (yes or no) on the accelerometer signal from wrist-worn biometric monitoring technology. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This report expands upon prior research [30,31], presenting a comprehensive application of an algorithm that captures step count and other aspects of mobility, such as walking cadence and bouts. We characterized the accuracy and reliability of this comprehensive set of digital walking measures from users wearing a wrist-worn device in real-world environments.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This report expands upon prior research [30,31], presenting a comprehensive application of an algorithm that captures step count and other aspects of mobility, such as walking cadence and bouts. We characterized the accuracy and reliability of this comprehensive set of digital walking measures from users wearing a wrist-worn device in real-world environments.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, we developed an algorithm that accurately classifies ambulatory status from data collected from a wrist-worn device, characterizing its performance across diverse demographic groups in a real-world setting [30]. Further, results from a substudy of an interventional randomized phase 2 trial demonstrated that digital measures of physical activity (step count and ambulatory time) could be sensitive to treatment effects in patients with Lewy body dementia [31].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose a protocol to study a wrist-worn device that can measure physical activity and physical capacity passively and remotely while performing assessments at home. The measurement properties of this device regarding physical activity are good but have been obtained in a healthy population [ 32 , 33 ]. We will extend these results and focus on the measurement properties of measuring physical capacity using the 6MWT in people with PD and COPD.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior work, we have developed algorithms whose outputs (measures for step counts and ambulatory time) demonstrated sensitivity to treatment effects in patients with Lewy Body Dementia [31]. We have also characterized the accuracy of an iteration of that algorithm in a cohort of diverse individuals in the real world [30].…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we developed an algorithm that accurately classifies ambulatory status from data collected from a wrist-worn device, characterizing its performance across diverse demographic groups in a real-world setting [30]. Further, results from a substudy of an interventional randomized phase-2 trial demonstrated that digital measures of physical activity (step count and ambulatory time) could be sensitive to treatment effect in patients with Lewy Body dementia [31].…”
Section: Introductionmentioning
confidence: 99%